2007
DOI: 10.1159/000103914
|View full text |Cite
|
Sign up to set email alerts
|

Structural Correlates of Apathy in Alzheimer’s Disease

Abstract: Background: Apathy is the most common noncognitive symptom inAlzheimer’s disease (AD). The structural correlates of apathy in AD have not yet been described. Methods: We analyzed magnetic resonance imaging data of 35 AD patients with and without apathy. Results: There was a significant linear association between apathy severity and cortical gray matter atrophy in the bilateral anterior cingulate [Brodmann area (BA) 24; r = 0.39–0.42, p = 0.01] and left medial frontal cortex (BA 8 and 9; r = 0.4, p < 0.02). Lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
2
2

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(124 citation statements)
references
References 45 publications
6
114
2
2
Order By: Relevance
“…Pathological data from Ad patients with severe dementia disclosed correlation between Acc pathology and apathy severity, according to NPI scores 52 . These findings were recently replicated in structural magnetic resonance imaging data 53 . Additionally, a series of studies with single photon emission tomography (sPecT) have shown resting hypometabolism in Acc from Ad apathetic patients when compared to non-apathetic individuals [54][55][56][57][58] .…”
Section: Apathy Alzheimer's Disease and Other Cortical Dementias: Nementioning
confidence: 62%
“…Pathological data from Ad patients with severe dementia disclosed correlation between Acc pathology and apathy severity, according to NPI scores 52 . These findings were recently replicated in structural magnetic resonance imaging data 53 . Additionally, a series of studies with single photon emission tomography (sPecT) have shown resting hypometabolism in Acc from Ad apathetic patients when compared to non-apathetic individuals [54][55][56][57][58] .…”
Section: Apathy Alzheimer's Disease and Other Cortical Dementias: Nementioning
confidence: 62%
“…More recent PET and resting fMRI studies in PD revealed an association between high apathy scores and abnormalities in several prefrontal regions (including orbitofrontal cortex, cingulated region, dorsolateral cortex, right middle frontal cortex), besides other cortical areas, such as bilateral inferior parietal gyrus, bilateral insula and right precuneus [65][66][67]. Also in AD, apathy severity has been associated with abnormalities in several cortical regions such as the anterior cingulate gyrus [68] and the left medial frontal cortex [69]. Taken together, these results indicated that apathy in neurodegenerative diseases seems to arise from altered functioning of several cortical areas, mainly of prefrontal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Brain imaging studies in AD reported a significant association between apathy and abnormal perfusion in the frontal cortex and in the cingulate area [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The functional neuroanatomy of apathy has been studied primarily in AD patients, where it was found that bilateral frontal, temporal, and cingulate area hypoperfusion and hypometabolism are associated with apathy severity [8][9][10][11][12]. Several structural neuroimaging studies also demonstrated an association between apathy and loss of integrity of frontal regions in AD [13,14]. Taken together, these results demonstrate that different brain areas are implicated in the pathophysiology of apathy in AD and suggest that circuits, rather than individual structures, may be disrupted in apathetic patients.…”
Section: Introductionmentioning
confidence: 99%